EVALUATION OF THE ANALGESIC EFFICACY AND SAFETY OF INTRATHECAL MORPHINE FOR POSTOPERATIVE PAIN MANAGEMENT AFTER COLON AND RECTAL RESECTION (Vietnam Journal of Community Medicine, 2026)
Background: Postoperative pain after colorectal surgery is often moderate to severe, negatively affecting early recovery. Intrathecal morphine is an effective analgesic technique, but its safety and efficacy in colorectal surgery in Vietnam remain limited.Objectives: To evaluate the analgesic efficacy and safety of intrathecal morphine in patients undergoing colorectal surgery.Methods: A prospective case series study was conducted on 38 patients undergoing colorectal surgery at 115 People’s Hospital from March to September 2025. All patients received 100 to 300 µg intrathecal morphine before general anesthesia. Pain scores (VAS) at rest and during movement at 4, 12, and 24 hours postoperatively, duration of effective analgesia (VAS < 4), intravenous morphine consumption, patient satisfaction, and adverse effects were recorded.Results: The mean duration of effective analgesia was 26.8 ± 5.4 hours. Mean VAS scores at rest at 4, 12, and 24 hours were 0.87, 1.03, and 1.76, respectively; during movement were 1.03, 1.63, and 2.66. The mean supplemental intravenous morphine dose within 24 hours was 2.8 mg, with 68.4% of patients requiring none. Patient satisfaction was high (92.1%). Adverse effects occurred in 34.2% of cases, mainly nausea/vomiting (25.6%) and pruritus (15.7%). No serious complications such as respiratory depression were observed.Conclusions: Intrathecal morphine at a dose of 100 - 300 µg provides effective and safe postoperative analgesia after colorectal surgery.
Keywords: Intrathecal morphine, postoperative pain management, colon and rectal resection.